Education policy reform and the return to schooling from instrumental variables - Kevin Denny; Colm Harmon (Institute for Fiscal Studies (IFS), 2000)
This paper analyses levels of low literacy across twelve countries using the International Adult Literacy Survey. We go beyond existing work that only looks at the proportions below certain critical levels of literacy. Using methods developed for the measurement of poverty we calculate measures of literacy that are sensitive to the distribution of literacy within those defined as illiterate. This reveals a different pattern of the extent of literacy problems across countries and within some populations. These measures should be useful to policy makers who need to allocate resources to alleviate low literacy and numeracy.
Keywords: 330; Bildungsertrag; Ausbildungsfinanzierung; Schule; Bildungsreform; Irland